Sources of energy for gating by neurotransmitters in acetylcholine receptor channels - Purohit, Prasad (National Academy of Sciences, 2012)
Nicotinic acetylcholine receptors (AChRs) mediate signaling in the central and peripheral nervous systems. The AChR gating conformational change is powered by a low- to high-affinity change for neurotransmitters at two transmitter binding sites. We estimated (from single-channel currents) the components of energy for gating arising from binding site aromatic residues in the α-subunit. All mutations reduced the energy (TyrC1>>TrpB≈TyrC2>TyrA), with TyrC1 providing ∼40% of the total. Considered one at a time, the fractional energy contributions from the aromatic rings were TrpB ∼35%, TyrC1 ∼28%, TyrC2 ∼28%, and TyrA ∼10%. Together, TrpB, TyrC1, and TyrC2 comprise an “aromatic triad” that provides much of the total energy from the transmitter for gating. Analysis of mutant pairs suggests that the energy contributions from some residues are nearly independent. Mutations of TyrC1 cause particularly large energy reductions because they remove two favorable and approximately equal interactions between the aromatic ring and the quaternary amine of the agonist and between the hydroxyl and αLysβ7.